Utilizing the Subunit Concept to Achieve Better Outcomes in Lower Limb Reconstruction: A Clinical Experience in an Asian Population - Qi En Hong, MBBS, MRCS, MMed (Surg)rmed; Jonah Ee Hsiang Kua, MBBS, MRCS, MMed (Surg), FAMS (plast Surg); Vincent K.S. Tay, MBBS, MRCS, MMed (Surg), FAMS (plast Surg); Stephanie L.S. Chan, MBBS, MRCS, MMed (Surg), FAMS (plast Surg); Christopher Wei Guang Ho, MBBS, MRCS, MMed (Surg), FAMS (plast Surg); Jeremy Mingfa Sun, MBBS, MRCSEd, MMed (Surg), FAMS (Plast Surg) (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. The goals of reconstruction have progressed from filling a defect to enhancing function and aesthetic appearance. We aimed to achieve better aesthetic and functional outcomes in terms of shoe fitting and mobility. This is accomplished via a classification of the subunits and aesthetic considerations of the lower limb. Methods:. Between April 2017 and December 2021, 66 cases of lower extremity free fasciocutaneous flap reconstruction cases were included in this retrospective study. Data parameters include age, sex, comorbidities, etiology of lower limb wounds, choice of free flap reconstruction, recipient arterial vessels, complications of flap reconstruction, and need for secondary debulking procedures. Physiotherapy records were also examined to determine the time to independent ambulation. Results:. In total, 66 subjects were identified. The mean age was 48.6. An estimated 74.2% (n = 49) were men, 50% (n = 33) had diabetes, and 16.6% (n = 11) had peripheral vascular disease. Of the total wounds, 65.1% (n = 43) were caused by infection, whereas the remaining 34.9% (n = 23) were due to trauma. Of the cases, 72.7% (n = 48) had free anterolateral thigh flap reconstruction, 25.8% (n = 17) were reconstructed with superficial circumflex iliac artery perforator flaps, and 1.5% (n = 1) was reconstructed with medial sural artery perforator flaps. Cases that required secondary debulking procedures comprised 7.6% (n = 5). Conclusions:. Free fasciocutaneous flaps are useful in lower extremity reconstruction. Based on the subunit principle and aesthetic considerations for lower limb reconstruction, it can aid in optimizing functional rehabilitation and decreasing secondary procedures.